Normal and knocking combustion of hydrogen: A numerical study. (15th July 2023) - Manzoor, Muhammad Umair; Yosri, MohammadReza; Talei, Mohsen; Poursadegh, Farzad; Yang, Yi; Brear, Michael
Abstract: This work presents a numerical study of normal and knocking combustion of hydrogen in a cooperative fuel research (CFR) engine. It is noteworthy that this study is the first to simulate this problem in a CFR engine. This engine has a significant relevance to spark-ignition engines as it is used to examine knock susceptibility of different fuels and explore fuel-engine interactions under a controlled environment. Using the Reynolds Averaged Navier Stokes (RANS) framework, a single compression ratio and four different spark timings are considered to investigate the transition from normal to knocking combustion. The results are validated against the experimental pressure trace data for both normal and knocking combustion. The model has been rigorously validated without changing the model constants across all cases. It is shown that for knocking cases an initial auto-ignition hotspot appears near the exhaust valve, where the unburned temperature is higher than the rest of the domain. A pressure wave then propagates, forming a secondary auto-ignition spot and two auto-ignitive flames eventually merge. The propagation speed of the auto-ignitive flame front is found to be 6–10 times higher than that of the premixed flame. Using the resonance theory of Bradley, the auto-ignition events are found to be in the developing detonation region. Furthermore, zero-dimensional homogeneous reactor simulations are shown to be suitable to predict the occurrence of auto-ignition in such engine, while 3-D RANS results are needed to accurately predict the pressure trace and auto-ignition timing. The results of this work also demonstrate how temperature stratification impacts the auto-ignition events. Highlights: This work features a first numerical model to simulate hydrogen normal and knocking in a CFR engine. RANS simulations with consistent model constants were able to capture the transition from normal to knocking combustion of hydrogen under lean conditions. Temperature stratification of the end gas led to auto-ignition of initial hotspots and consequent pressure waves caused multiple auto-ignitions. The auto-ignition events are found to be in the developing detonation region, according to Bradley's resonance theory. A simple zero-dimensional model can capture the auto-ignition event.